Índice de meios de vida e desenvolvimento rural sustentável em assentamento rural no município de Simão Dias/SE - Santana, Millena dos Santos (2024)
Rural settlements from the agrarian reform movement are essential for expanding and strengthening family farming - which is the basis for achieving Sustainable Rural Development (SRD). However, for this contribution to be effective, new approaches, instruments and strategies are needed to lead them to higher levels of SRD. In this context, the study aimed to analyze the Livelihood Index and its relationship with sustainable rural development in rural establishments in the Oito de Outubro settlement, in the municipality of Simão Dias/SE. To this end, the study is of a quantitative-qualitative nature and consists of the following methodological stages: characterization of the area studied; bibliographical and documentary research; bibliometric research; survey research and quantitative-qualitative analysis of the data through the construction of the Livelihoods Index (LVI) and lexical analysis. A semi-structured interview script was used as a data collection tool, aimed at a sample of 19 establishments. From the bibliometric research, 66 articles were found, of which only seven were selected after quality assessment. The majority of the articles selected only partially address the issue of livelihoods in rural settlements. The results point to the need for additional research that directly explores livelihoods in different rural territories. The survey revealed that the social dimension has the greatest potential to contribute to the livelihoods of settlements, with an average of 7.74, highlighting the importance of human and social capital. In contrast, the environmental and economic dimensions had lower averages, 7.15 and 7.02 respectively, indicating significant limitations. In addition, the IMV of the establishments studied demonstrates the settlement's potential in relation to the DRS; however, there is a need for a more balanced distribution of resources, especially environmental resources. Finally, the qualitative research highlighted the predominance of corn monoculture due to factors such as security and commercial viability, but this practice increases farmers' vulnerability and degrades natural resources. Based on the results obtained, it can be concluded that in order to achieve higher levels of DRS, it is essential to adopt integrated strategies that promote a more balanced distribution of resources and diversification of agricultural practices, thus strengthening the livelihoods of family farmers in the Oito de Outubro settlement.